GAMBARAN PENGETAHUAN IBU TENTANG PEMBERIAN MPASI DI KELURAHAN AEK MANIS KOTA SIBOLGA TAHUN 2022 - rangkuti, nur aliyah; Insan, Hafni Nur; Nasution, Ayyanur; Sodikin, Muhammah Ali (Jurnal Kesehatan Ilmiah Aufa Royhan, 2023)
ABSTRACT The problem of providing complementary feeding id strongly influenced by health behaviour (over behaviour) or actions. The overage rate of exclusive breastfeeding in the world is only around 50%. North Sumatera Province in 2018 the proportion of breastfeeding patterns for infants aged 0-5 months was 50% exclusive breastfeeding. The purpose of this study was to deytermine the description of maternal knowledge about the provision of complementary foods in Aek Manis Village Sibolga 2022. The type of research was quantitiative with a descriptive design. The population in this study were all mothers who had babies aged 6-12 months in Aek Manis Village as many as 42 people with a total sample technique. The analysis used was univariate analysis. The results of this study indicate that the majority are aged 20-35 years as many as 17 people (40,5%), and the education of the majority of respondents was in junior high school as many as 14 people (33.3%). Respondents lack of knowledge as many as 19 people (45,2%), good knowledge as many as 12 people (28,6%) and succifient knowledge as many as 11 people (26,2%). The conclusion was that the majority of responbdents’ knowledge was lack. It was hoped that health workers will be more active in providing promotions and counselling related to MPASI. ABSTRAK Masalah Pemberian Makanan Pendamping ASI sangat dipengaruhi oleh perilaku kesehatan (over behaviour) atau tindakan. Rata-rata angka pemberian ASI eksklusif di dunia baru berkisar 50%. Provinsi Sumatera Utara tahun 2018 proporsi pola pemberian ASI pada bayi umur 0-5 bulan sebanyak 50% ASI Eksklusif. Tujuan penelitian ini untuk mengetahui Gambaran Pengetahuan Ibu Tentang Pemberian MPASI Di KelurahanN Aek Manis Kota Sibolga Tahun 2022. Jenis penelitian kuantitatif dengan desain deskriftif. Populasi dalam penelitian ini adalah semua ibu yang mempunyai bayi usia 6- 12 bulan yang ada di Kelurahan Aek Manis sebanyak 42 orang dengan tehnik total sampel. Analisa yang digunakan ada;ah analisa univariat. Hasil penelitian ini menunjukkan mayoritas berusia 20-35 tahun sebanyak 17 orang (40,5%). Dan pendidikan responden mayoritas SMP sebanyak 14 orang (33,3%). Pengetahuan responden kurang senayak 19 orang (26,2%) dan pengetahuan cukup sebanyak 11 orang (26,2%). Kesimpulan mayoritas pengetahuan responden kurang, diharapkan kepada petugas kesehatan agar lebih aktif dalam memberikan promosi dan peyuluhan terkait MPASI.